2017
DOI: 10.2147/amep.s138467
|View full text |Cite
|
Sign up to set email alerts
|

A 15-year review of the Stanford Internal Medicine Residency Program: predictors of resident satisfaction and dissatisfaction

Abstract: IntroductionSatisfaction with training and with educational experiences represents important internal medicine (IM) programmatic goals. Graduates from IM residency programs are uniquely poised to provide insights into their educational and training experiences and to assess whether these experiences were satisfactory and relevant to their current employment.MethodsWe surveyed former IM residents from the training program held during the years 2000–2015 at the Department of Medicine, Stanford University. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Burnout among physicians is reported to be associated with reduced learning capacity,[ 15 ] stress-related health problems,[ 16 ] emotional exhaustion (EE), and low sense of professional efficacy. [ 17 ] Adverse personal consequences including substance abuse, depression, family conflicts, and suicidal ideation[ 3 18 19 ] has also followed professional burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Burnout among physicians is reported to be associated with reduced learning capacity,[ 15 ] stress-related health problems,[ 16 ] emotional exhaustion (EE), and low sense of professional efficacy. [ 17 ] Adverse personal consequences including substance abuse, depression, family conflicts, and suicidal ideation[ 3 18 19 ] has also followed professional burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Notable associations which were correlated with residency dissatisfaction were highlighted, including wanting “more or much more” time available to spend with family and insufficient patient interactions. 1 It was found that ~40% of the participants reported wanting to spend more time with family. 1 Lu et al 2 similarly found that satisfaction among health care staff was increased by balancing adequate time between work and family.…”
Section: Dear Editormentioning
confidence: 99%
“… 1 It was found that ~40% of the participants reported wanting to spend more time with family. 1 Lu et al 2 similarly found that satisfaction among health care staff was increased by balancing adequate time between work and family. We believe that Lu et al’s 2 study may be extrapolated to other cohorts, including medical students.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Residency programs differ in case diversity, resident autonomy, workload, service expectations, structure, supervision, and other factors that influence the educational experience. Recent publications 1 , 2 , 3 , 4 , 5 examined resident well-being, but literature on program satisfaction is limited, 6 , 7 particularly in radiation oncology (RO). 8 , 9 Information on the general work environment, call responsibilities, average workweek, and adequacy of ancillary support 9 , 10 is valuable for medical students who are selecting a residency program 7 and for institutions seeking benchmarks when evaluating their own programs.…”
Section: Introductionmentioning
confidence: 99%